Global and local area inspection methods in damage detection of carbon fiber composite structures. (January 2022) - Balasubramaniam, Kaleeswaran; Fiborek, Piotr; Ziaja, Dominika; Jurek, Michał; Sawczak, Mirosław; Soman, Rohan; Malinowski, Paweł H.
Highlights: Impact damage in composite structures was analyzed with global area and local area inspection methods. The damage localization was performed using guided wave based sectoral elliptical code. Infrared thermography based crack shape identification algorithm was newly developed. Crack size and growth severity was quantified using improved ultraviolet radiation based tracer dye. Impact crack damage location, shape and size were quantified. Abstract: The paper presents multiple impact damage detections and characterization in a multi-layered carbon fiber reinforced polymer structure using a multi-step combination of the global area and local area damage detection methods. A global area analysis using laser Doppler vibrometer (LDV) with piezoelectric lead zirconate titanate (PZT) actuator-based guided waves (GW) excitation was used to detect and locate the damage. The GW full wavefield (FWF) mode conversion and root mean square (RMS) based LDV studies helped to visualize the impact crack damage (ICD) when tested at varying excitation frequencies. The experimental results were cross-verified numerically using the spectral element method (SEM). The implemented structural health monitoring (SHM) based sectorial elliptical code (SEC) reduced the overall calculation time in damage localization and accurately identified the damage from experimental and numerical data. An infrared thermography (IRT)-based crack identification algorithm was developed in pinpointing the ICD shape. The automatic method removes the influence of high heat sources and highlights the damage zones easily. The accuracy of the localization strategy was successfully verified with non-contact active IRT analysis. The crack size and damage severity were quantified using the ultraviolet radiation (UVR) method with a solution mixture based organic dye. The global area method allows detecting possible damage, validated and quantified with the non-destructive testing (NDT) techniques.